2015
DOI: 10.1017/s0950268815000990
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial association of Streptococcus suis infection in humans and porcine reproductive and respiratory syndrome outbreaks in pigs in northern Vietnam

Abstract: SUMMARYPorcine reproductive and respiratory syndrome (PRRS) outbreaks in pigs are associated with increased susceptibility of pigs to secondary bacterial infections, including Streptococcus suis – an important zoonotic pathogen causing bacterial meningitis in humans. This case-control study examined the association between human S. suis infection and PRRS outbreaks in pigs in northern Vietnam. We included 90 S. suis case-patients and 183 non-S. suis sepsis controls from a referral hospital in Hanoi in 2010, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…There were 682 records remaining after removing duplicates in which 636 citations that were proceedings or did not contain risk factors were excluded upon title and abstract screening. There were 32 articles included in systematic review 5 , 9 – 11 , 13 – 40 and 3 case-control studies 19 , 37 , 38 in the meta-analysis after full texts evaluation. The PRISMA flow chart describing the study selection process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 682 records remaining after removing duplicates in which 636 citations that were proceedings or did not contain risk factors were excluded upon title and abstract screening. There were 32 articles included in systematic review 5 , 9 – 11 , 13 – 40 and 3 case-control studies 19 , 37 , 38 in the meta-analysis after full texts evaluation. The PRISMA flow chart describing the study selection process was shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies with different study designs were conducted in 9 distinctive countries. Among these, there were 1 randomized double-blind, placebo-controlled trial 10 , 3 case-control studies in which there were 1 matched case-control 37 , 1 retrospective case-control 38 and 1 prospective case-control studies 19 , 28 descriptive studies including 3 public health surveillance studies 27 , 40 , 41 , 2 outbreak investigations 36 , 39 and 1 epidemiological analysis in China 23 , a population-based study on a food safety campaign 30 and a retrospective cohort identifying risk factor for S . suis mortality 34 , 3 retrospective reviews 16 , 20 , 21 and 17 case reports or case series 9 , 11 , 13 – 15 , 17 , 18 , 22 , 24 – 26 , 28 , 29 , 31 – 33 , 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a public health point of view, it has been suggested that infection of PRRS in pigs was increased by co-infection with Streptococcus suis (S. suis) [28,29], further to one experiment that showed that PRRS infected pigs were more susceptible to S. suis [30]. In Vietnam, some studies showed that significantly more cases of S. suis were observed in a district adjacent to a PRRS district [31,32]. S. suis infection is a zoonotic disease of growing importance in Asia that causes acute meningitis, septicemia and arthritis in humans [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus suis infection has nonspecific clinical symptoms in the early stages and progresses rapidly. Mortality rates (0-33.3%) are low compared with meningitis caused by other pathogens (5)(6)(7)(8)(9)(10)(11)(12). However, toxic shock-like syndrome caused by this pathogen has a high mortality rate in China (62 and 50%) and Thailand (80%) (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%